Tax compliance and privacy rights in profiling and automated decision making - Luisa Scarcella (Internet Policy Review, 2019)
New technologies allow tax authorities to carry out faster and automated analysis of large amounts of data, minimising errors and saving time. Some of these technologies enable tax administrations to identify and cluster taxpayers based on the risk of noncompliance. Consequently, "high risk" taxpayers will be audited. The European Union General Data Protection Regulation (GDPR) has introduced new provisions on automated decision making and how individuals can be profiled - technology, such as the one implemented by tax administrations, could present difficulties in this area. Even if profiling and automated decision making in tax matters are included in the broader public interest exception, safeguards to taxpayers' privacy rights need to be in place.
Keywords: 300; Taxation; Profiling; Automated decision-making; GDPR